Inhibitory effects of resveratrol on orthodontic tooth movement and associated root resorption in rats. (March 2020) - Liu, Xiao-can; Wang, Xu-xia; Zhang, Li-na; Yang, Fan; Nie, Fu-jiao; Zhang, Jun
Highlights: Resveratrol inhibits orthodontic tooth movement in Wistar rats. Resveratrol inhibits orthodontic induced root resorption. Resveratrol reduces TRAP-positive cells on the pressure side of the root. Resveratrol reduce the expression of RANKL and increase the expression of OPG, RUX2, and OCN. Abstract: Objective: To investigate the effect of resveratrol (RSV) on orthodontic tooth movement (OTM) and orthodontic induced root resorption (OIRR) in rats. Methods: Thirty-six male Wistar rats used in this study were randomly divided into three groups of 12 animals each. All test subjects underwent a 50 g orthodontic force each, generated from a nickel-titanium closed-coil spring. The control group were fed carboxymethylcellulose (CMC) while rats in other two groups were fed 5 mg/kg/d RSV or 10 mg/kg/d RSV (dissolved in CMC). After 14 days of OTM, all rats were sacrificed, after which each group was randomly divided into two subgroups (6 test subjects in each subgroup). One subgroup was used to measure the amount of OTM and assessed by hematoxylin and eosin (HE) staining, tartrate-resistant acid phosphatase (TRAP) staining, and immunohistochemistry staining of Receptor Activator of Nuclear Factor-κ B Ligand (RANKL), Osteoprotegerin (OPG), Runt-related transcription factor 2 (RUNX2), as well as Osteocalcin (OCN). The second subgroup was used to analyze OIRR via scanning electron microscopy. Results: Compared with the control group, the RSV groups showed a significant decrease in the distance of OTM and the OIRR ratio ( p ＜0.05). The number of TRAP positive osteoclasts and the expression of RANKL in periodontal tissue of the RSV groups were significantly inhibited ( p ＜0.01) while the expression of OPG, RUNX2, and OCN were remarkably promoted ( p ＜0.05). The effect of 10 mg/kg/d RSV group was more obvious than that of 5 mg/kg/d RSV group ( p ＜0.05). Conclusions: RSV could reduce the extent of OTM and root resorption areas.